2019
DOI: 10.3389/fphar.2019.00915
|View full text |Cite
|
Sign up to set email alerts
|

Screening Bioactive Compounds of Siraitia grosvenorii by Immobilized β2-Adrenergic Receptor Chromatography and Druggability Evaluation

Abstract: As the first and key step of traditional Chinese medicine (TCM)-guided drug development, lead discovery necessitates continuous exploration of new methodology for screening bioactive compounds from TCM. This work intends to establish a strategy for rapidly recognizing β 2-adrenergic receptor (β 2-AR) target compounds from the fruit of Siraitia grosvenorii (LHG). The method involved immobilization of β 2-AR onto amino-microsphere to synthesize the receptor column, the combination of the column to high-performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A study established an affinity chromatography strategy to evaluate the anti-asthmatic effects of SGEs using immobilized toxomatine 3 acetylcholine receptor (M3R). The results showed that the flavor components in SGEs that bind to this receptor are Mog V and 11-O-Mog V. The anti-asthmatic effects of these ingredients when used in concert were more significant than SGEs alone ( Jia et al, 2019 ). These findings collectively underscore the promise of Mog V and 11-O-Mog V as candidates for functional food additives.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…A study established an affinity chromatography strategy to evaluate the anti-asthmatic effects of SGEs using immobilized toxomatine 3 acetylcholine receptor (M3R). The results showed that the flavor components in SGEs that bind to this receptor are Mog V and 11-O-Mog V. The anti-asthmatic effects of these ingredients when used in concert were more significant than SGEs alone ( Jia et al, 2019 ). These findings collectively underscore the promise of Mog V and 11-O-Mog V as candidates for functional food additives.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…While, glycosides of the 11a-hydroxy series (R4: a-OH) taste sweet, while mogrosides I, mogrosides II, glycosides of the 11b -hydroxy (R4: b -OH) are tasteless; dehydro derivatives and 11-oxo compounds (more in unripe fruit) taste bitter (Kasai et al, 1988). In addition, a novel iso-mogroside V has been identified with high potency sweetener (500 times sweeter than sucrose) and flavor enhancer (Jia and Yang, 2014).…”
Section: Impact Of Natural Noncalorie Sweetenermentioning
confidence: 99%
“…Several studies have examined that the administration of mogrosides derived from the monk fruit exhibited inhibitory response against the inflammation. Mogroside V is the key compound involved in declining the inflammatory effects in asthma ensuring efficient drug ability properties for the preparation of new drug-combating b 2AR-mediated respiratory ailments (Jia et al, 2019). Likewise, studies have shown the shielding action of mogroside V on the ovalbumin-induced experimental asthma caused by allergy in the mice.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…immobilized β 2 ‐adrenoceptor ( β 2 ‐AR), an important drug target for respiratory diseases, onto macroporous silica gel by various immobilization methods [15–18]. The affinity columns were used to screen the bioactive compounds from TCMs, such as Siraitia grosvenorii [19] and Rhodiola crenulate [20]. They identified rosamaric acid, mogroside V, and salidroside as the bioactive compounds in the three herbal medicines that target β 2 ‐AR, respectively.…”
Section: Introductionmentioning
confidence: 99%